(untitled) (UNED Research Journal, 2026)
Introduction: There are no studies on the consumption of sapote (Pouteria sapota). Objective: To qualitatively characterize the consumption of sapote in five cities in Costa Rica. Methods: We conducted the research in the cities of San José, Alajuela, Heredia, Cartago, and Liberia, between April and December 2019. We conducted 640 personal interviews on various topics related to knowledge about this fruit and its consumption. Results: In Liberia, we found a higher level of knowledge about sapote (86% of respondents) and higher consumption of this fruit (66%), compared to the other cities studied (71-80%, and 31-42%, respectively). In the five cities, the preference for sapote consumption was reported by 28-71% of women and 26-60% of men, as well as by 19-38% of people between 15-29 years old, 25-68% of people between 30-44 years old, 34-78% of people between 45-59 years old, and 34-97% of people between 60-99 years old. In all five cities, most people who consumed sapote did so once or twice a year. In San José, Alajuela, and Liberia, the main place to buy this fruit was the farmers’ market, while in Heredia and Cartago it was the supermarket. In San José, Alajuela, Heredia, and Liberia, sapote was primarily considered to be fairly priced, but in Cartago, it was largely considered expensive. The main characteristics associated with a quality sapote fruit were: red or orange pulp, sweet or very sweet flavor, soft pulp, large size, good flavor, and no bruises, cracks or damage. In all five cities, the main form of consumption of sapote was as fresh fruit. Conclusion: The study reveals that there is a significant level of sapote consumption among the young population in the five cities studied. Furthermore, this work represents the first systematic analysis of the characterization of sapote consumption in Costa Rica, which will provide relevant information for future strategies to promote and conserve this species.